The Influence of Debt Policy and Investment Decisions on Company Value with Dividend Policy as a Moderating Variable (Empirical Study on LQ 45 Companies Listed on the IDX) - Suryami; Zulfa Rosharlianti (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2025)
This study aims to analyze the effect of debt policy and investment decisions on firm value, with dividend policy as a moderating variable. This research is quantitative and uses secondary data in the form of audited annual financial statements sourced from the official website of the Indonesia Stock Exchange (IDX). The population consists of 45 LQ45 companies listed on the IDX during the 2020–2024 period. Purposive sampling was employed to select 16 companies that met the criteria, which were observed over a five-year period. Data analysis was conducted using panel data regression and moderated regression analysis with EViews 12 software. The results indicate that debt policy partially affects firm value, and investment decisions affect firm value. Dividend policy does not moderate the effect of debt policy on firm value, whereas dividend policy does moderate the effect of investment decisions on firm value